Dampak Teknologi Finansial Dalam Perbankan Syariah: Pendekatan Kualitatif Terhadap Perubahan Paradigma Dan Tantangan - Diva Khalishah Mutiara; Madian Muhammad Muchlis (STIKes Ibnu Sina Ajibarang, 2024)
This research investigates the impact of financial technology in Islamic banking through a qualitative approach. The primary focus is on the paradigm shift in operational processes and challenges faced by Islamic financial institutions in adopting technological innovations. Through the analysis of regulations, financial technology implementation, and stakeholder perceptions, this study identifies significant changes in financing and investment models. Findings indicate positive impacts such as increased operational efficiency, product diversification, and responsiveness to consumer demands. However, challenges in data security and unequal access emerge as primary concerns. This research provides in-depth insights into how financial technology triggers transformation in Islamic banking, with significant implications for regulatory design and future business strategies.